2016
DOI: 10.1155/2016/4393127
|View full text |Cite
|
Sign up to set email alerts
|

Variables That Best Differentiate In-Patient Acute Stroke from Stroke-Mimics with Acute Neurological Deficits

Abstract: Introduction. Strokes and stroke-mimics have been extensively studied in the emergency department setting. Although in-hospital strokes are less studied in comparison to strokes in the emergency department, they are a source of significant direct and indirect costs. Differentiating in-hospital strokes from stroke-mimics is important. Thus, our study aimed to identify variables that can differentiate in-hospital strokes from stroke-mimics. Methods. We present here a retrospective analysis of 93 patients over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…These differences were not found in true stroke (EoSC CVA+) patients. We found diabetes to be the only significant factor to predict stroke within the EoSC CVA+ cohort (using Definition 2) but did not find the expected correlation with AFib or cardiac history [8]. These findings may be due to the resultant small eventual sample size of EoSC diagnosed CVA+ patients.…”
Section: Discussionmentioning
confidence: 99%
“…These differences were not found in true stroke (EoSC CVA+) patients. We found diabetes to be the only significant factor to predict stroke within the EoSC CVA+ cohort (using Definition 2) but did not find the expected correlation with AFib or cardiac history [8]. These findings may be due to the resultant small eventual sample size of EoSC diagnosed CVA+ patients.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the NIHSS may help exclude stroke mimics (39). Several studies show that alternate diagnoses are found in 22 to 38% of suspected stroke cases (40)(41)(42). It is essential to distinguish stroke from notable mimics since rtPA administration not only exposes the patient Haldal et al…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…Notable stroke mimics include seizure, encephalopathy, syncope, migraine, sepsis, and toxic/ metabolic derangements (42). Compared to mimics, stroke is more likely if a patient has almost any focal neurological symptom, such as subjective hand weakness or objective hemiparesis (42).…”
Section: Clinical Diagnosismentioning
confidence: 99%
See 2 more Smart Citations